1999
DOI: 10.1152/ajpendo.1999.276.2.e326
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the regulation of key enzymes of cysteine metabolism in rat liver in vivo

Abstract: Little is known about mechanisms of regulation of cysteine dioxygenase (CDO), γ-glutamylcysteine synthetase (GCS), and cysteine-sulfinate decarboxylase (CSDC) in response to diet. Enzyme activity and Western and Northern or dot blot analyses were conducted on liver samples from rats fed a basal low-protein diet or diets with graded levels of protein or methionine for 2 wk. Higher levels of CDO activity and CDO protein but not of CDO mRNA were observed in liver of rats fed methionine or protein-supplemented die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 24 publications
12
62
1
Order By: Relevance
“…Protein was concentrated on Vivaspin centrifugation concentrators (GE Healthcare) to the appropriate concentrations for the subsequent experiments. As expected, P. aeruginosa CDO homologue preparations resolved into a single band when subjected to SDS-PAGE, revealing the absence of a posttransla-tional modification present in mammalian CDO (53)(54)(55)(56) (Fig. 3).…”
Section: Methodssupporting
confidence: 64%
“…Protein was concentrated on Vivaspin centrifugation concentrators (GE Healthcare) to the appropriate concentrations for the subsequent experiments. As expected, P. aeruginosa CDO homologue preparations resolved into a single band when subjected to SDS-PAGE, revealing the absence of a posttransla-tional modification present in mammalian CDO (53)(54)(55)(56) (Fig. 3).…”
Section: Methodssupporting
confidence: 64%
“…Thus, although most of the body's hypotaurine/taurine pool is in the form of taurine, hypotaurine is a better indicator of active taurine biosynthesis. Previous work has shown that CDO activity plays the major role in determining the flux of cysteine to hypotaurine/taurine (1,2,5). Cysteinesulfinate decarboxyase, which catalyzes the decarboxylation of cysteinesulfinate to hypotaurine, is highly expressed in pancreas and kidney as well as in liver (24).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, our results showed that cysteine supplementation significantly decreased the proportion of protein-bound homocysteine and increased the proportion of non-proteinbound homocysteine in the plasma of rats fed 15S (experiment 3). The lack of cysteine supplementationinduced increase in plasma cysteine concentration observed in rats fed 25C and 25S appears to be due to higher activities of cysteine dioxygenase, the rate-limiting enzyme of cysteine metabolism (1), since it has been shown that the activity of this enzyme increases in response to increase in dietary levels of protein and sulfur amino acids such as methionine and cysteine (35,36).…”
Section: Discussionmentioning
confidence: 99%